PERAN PENDIDIKAN DASAR DALAM PEMBENTUKAN KARAKTER ANAK - Irnanda, Ela; Nuria, Sarda; Desyandri, Desyandri; Jamaris, Jamaris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article uses a meta-analysis method to investigate the extent to which character education in elementary schools. This research uses a meta-analysis approach with a focus on qualitative research that has been conducted previously. A qualitative research design, through case studies, was used to understand the experiences, perceptions and effectiveness of character education for elementary school children. The research population involved elementary school students, parents, and teachers. The sample was selected purposively by taking into account variations in characteristics such as age, gender and socio-economic background. Data was collected through interviews, observation and documentation. Interviews were conducted with teachers, parents and students. Observation involves observing the implementation of character education in the school environment. Data is also collected through documentation of character education activities that have been implemented. Research shows that character education for elementary school children has a positive impact in shaping children's character. Integrating character education material into subjects, self-familiarization activities, and creating a conducive school environment are effective strategies.